Health Benefits of a Vegan Diet: Current Insights - Radnitz, Cynthia; Ni, Jingwen; Dennis, Danielle; Cerrito, Brianna (Nutrition and dietary supplements, 2020)
: To assess the health benefits of a vegan diet, observational studies of diabetes (non-insulin dependent; NIDDM), cancer, mortality, gut microbiota, hypertension, lipids, and overweight were examined. Utilizing PRISMA items to identify articles and assess their quality for inclusion, 44 studies were screened into the review. In two separate studies, vegans did not have a reduced risk of diagnosis of "any" cancer, nor of specific cancers when the effects of BMI were adjusted. When data were aggregated, there was a reduced risk of any cancer. Vegans had lower total cholesterol and LDL-C levels compared to omnivores, and in some cases other dietary groups. In the US, there was a reduced risk of a diagnosis of NIDDM and in Western countries, vegans had lower BMI. Research support for reduced risk of diagnosis of female cancers, improved mortality rates, lower blood pressure, lower triglycerides, and a healthier microbiome for vegans compared to omnivores was inconsistent. There was no evidence that reduced specific cancer incidence rates were lower in vegans although inadequate sample sizes had hampered these analyses. In vegans, HDL-C levels were either lower or not significantly different from omnivores. Geographic location was a strong moderator with the most compelling evidence for the health advantages of a vegan diet coming from the US, whereas in Taiwan, India and Vietnam, there was much less evidence of its benefit. In some instances, sex moderated the association between adopting the diet and health outcomes. Adherence, specific content of the diet, and dietary comparison groups utilized in studies may also affect results. Although a vegan diet is associated with some health benefits, the level of support for the benefit varied according to the health outcome being measured, with evidence emerging that BMI is an important mediator and geography and to a lesser extent sex are important moderators. Keywords: vegan, vegetarian, health